'Excessive sweating is not a feminine thing': A qualitative study of women's experiences suffering from primary hyperhidrosis. - Alexander Shayesteh; Margareta Persson; Christine Brulin; Elisabet Nylander (PLoS ONE, 2021)
Background Primary hyperhidrosis, excessive focal sweating is a common disease equally affecting men and women. Women tend to seek care more often and assess being more affected by hyperhidrosis in their daily life. The aim of this study was to explore experiences of living with primary hyperhidros in a sample of 15 women. Methods Individual, semi-structured interviews with a purposive sample of 15 women diagnosed with primary hyperhidrosis and analysed by qualitative content analysis utilising an inductive approach. Results The analysis resulted in a theme, constantly guarding the female image, based on three categories, misfitting the feminine norms, avoiding the attention of others and passing like any woman. Primary hyperhidrosis in women disrupted the ideal feminine appearance. Wearing clothes that concealed hyperhidrosis and distancing from social gatherings, in combination with negative remarks by others, created stress and anxiety and had a negative effect on self-esteem. Women felt poorly understood by others regarding the extent of their sweating and were misunderstood in intimate situations while trying to reduce the sweat production. Choices regarding education and career opportunities were affected, since being exposed and receiving attention due to primary hyperhidrosis was unwanted. Treatment with botulinum toxin liberated women from excessive sweating and removed a social handicap they described living with. Conclusion Primary hyperhidrosis in women disrupts the feminine appearance, lowers self-esteem and hinders social interactions. Clinicians assessing primary hyperhidrosis need to be aware that women may report the impairments from primary hyperhidrosis as being more associated with body image and appearance than with functional reductions in daily life. Educating patients, providing accurate information regarding the disease via media and cooperating with patient groups are important for increasing awareness and achieving progress in care for women with primary hyperhidrosis.